Narrativas amazônicas: do Carnaval à literatura - Marcia Caetano Langfeldt (Centre de Recherches sur les Mondes Américains, 2019)
Since the discovery of the Amazon, the region has been represented in different ways, mainly through travelogues. The aim of this thesis is to analyze the representations of the Amazon, from the early twentieth century to the present, through the point of view of Brazilian authors, evaluating to what extent these representations incorporate or reject the point of view of these multiple travel writings. In this context, the analysis focuses on the relationship between literature, science and national identity. The purpose is to examine how these forms of discourse compete in constituting the national ethos in a crucial period of self-determination for Brazil.